Systematic Literature Review Tentang Loyalitas Nasabah Bank Syariah Di Indonesia - Lubis, Muhammad Arif Fadhillah; Muthmainnah, Muthmainnah (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2023)
In the current era of competition in the banking industry, customer loyalty is a key factor in the existence of Islamic banks. Not a few research results show that customer loyalty among Islamic banks simultaneously influences the increase in profits of Islamic banks so that they can gain a wider market share. This article aims to examine journal papers that discuss customer loyalty in Islamic banks. This study used the systematic literature review (SLR) method with samples in the form of secondary data from journals that were searched through the Google Scholar database. The research results from the Systematic Literature Review show that the Islamic bank that has been studied the most by researchers is Bank Syariah Indonesia (BSI). The most widely used data collection technique was a questionnaire. The factor that most influences customer loyalty is service quality, followed by customer satisfaction.